The impact of sleep problems on cerebral aneurysm risk is mediated by hypertension: a mediated Mendelian randomization study - Yan, Xiaofei; Li, Hongwu (Frontiers in Genetics, 2024)
Introduction: Cerebral aneurysm (CA) is a common vascular disease. The risk factors of CA include hypertension, smoking, and a family history of genetic predisposition. Although sleep-related problems have been found to have a strong association with cardiovascular disease, there is a lack of research regarding the causal relationship with cerebral aneurysms. Methods: In this study, we investigated the causal relationship between four sleep-related problems, including snoring, insomnia, narcolepsy, and napping during the day, and CA using a two-sample Mendelian randomization (MR) analysis. Moreover, the potential confounders before sleep problems and CA were further analyzed by multivariate MR (MVMR). Results: The causal relationship between insomnia and CA was obtained analytically by means of six MR analyses. There was a strong causal effect relationship between insomnia and CA, which suggests this as a potential risk factor (odds ratio (OR) = 8.35, 95% confidence interval (CI) = 2.422-28.791, p = 7.772e-04). On this basis, hypertension was identified as a mediator between insomnia and CA by MVMR, with a mediating effect of 52.538% (OR = 3.05, 95% CI = 1.549-4.55, p = 0.015). Conclusion: The causal relationship between insomnia and CA was predicted using genetic variance data, and insomnia was found to be a potential risk factor. Furthermore, hypertension is a mediator between insomnia and CA. Therefore, focusing on sleep problems and improving sleep quality may be an active and effective strategy to prevent CA.